Parents know it best: Prediction of asthma and lung function by parental perception of early wheezing episodes. Issue 8 (2nd October 2019) - Brick, Tabea; Hose, Alexander; Wawretzka, Katharina; von Mutius, Erika; Roduit, Caroline; Lauener, Roger; Riedler, Josef; Karvonen, Anne M.; Pekkanen, Juha; Divaret‐Chauveau, Amandine; Dalphin, Jean‐Charles; Ege, Markus J.; et al.
Abstract: Background: Childhood asthma is often preceded by early wheeze. Usually, wheezing episodes are recorded retrospectively, which may induce recall bias. Aims and objectives: The aim of this study was to investigate true‐positive recall of parent‐reported wheeze at 1 year of age, its determinants, and its implications for asthma and lung function at 6 years of age. Methods: The PASTURE (Protection Against Allergy—Study in Rural Environments) study followed 880 children from rural areas in 5 European countries from birth to age 6 years. Wheeze symptoms in the first year were asked weekly. At age 6, parent‐reported asthma diagnosis was ascertained and lung function measurements were conducted. Correct parental recall of wheeze episodes at the end of the first year was assessed for associations with lung function, asthma, and the asthma risk locus on chromosome 17q21. Results: Parents correctly recalled wheeze after the first year in 54% of wheezers. This true‐positive recall was determined by number of episodes, timing of the last wheeze episode, and parental asthma. Independently from these determinants, true‐positive recall predicted asthma at age 6 years (odds ratio 4.54, 95% confidence interval (CI) [1.75‐14.16]) and impaired lung function (β = −0.62, 95% CI [−1.12; −0.13], P ‐value = .02). Associations were stronger in children with asthma risk SNPs on chromosome 17q21. Conclusion: Correct parental recall of wheezing episodes may reflect clinical relevance of early wheeze and its impact on subsequent asthma and lung function impairment. Questions tailored to parental perception of wheezing episodes may further enhance asthma prediction. Abstract :